Pengaruh Dana Pihak Ketiga (DPK), Non Performing Loan (NPL) Dan Loan To Deposit Ratio (LDR) Terhadap Penyaluran Kredit (Pada PT. Bank Perkreditan Rakyat di Kabupaten Bogor Periode 2018-2022) - Rahmayanti, Indri Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to determine the influence of Third Party Funds (DPK), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR) on partial and simultaneous credit distribution at PT Bank Perkreditan Rakyat in Bogor Regency for the 2018-2022 period. and To find out how much contribution Third Party Funds (DPK), Non Performing Loans (NPL), and Loan to Deposit Ratio (LDR) have made to partial and simultaneous credit distribution at PT Bank Perkreditan Rakyat in Bogor Regency for the 2018-2022 period. This research uses a quantitative research design with a causal relationship approach. In this research, credit distribution is the dependent variable. Meanwhile, the independent variables in this research are Third Party Funds (DPK), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR). The research results show that based on the calculation of the coefficient of determination (R Square), a value of 0.887 is obtained. This result means that there is a contribution of 88.7% from the independent variables Third Party Funds (DPK), Non Performing Loans (NPL), and Loan to Deposit Ratio (LDR) to credit distribution at PT Bank Perkreditan Rakyat in Bogor Regency for the 2018 period. -2022.